Genetic variants at 9p21.3 are associated with risk of esophageal squamous cell carcinoma in a Chinese population. Issue 2 (February 2017) - Lin, Xiaoming; Yan, Caiwang; Gao, Yong; Du, Jiangbo; Zhu, Xun; Yu, Fei; Huang, Tongtong; Dai, Juncheng; Ma, Hongxia; Jiang, Yue; Yin, Rong; Hu, Zhibin; et al.
Abstract : Genome‐wide association studies have linked genetic variants at 9p21.3 to the risk of multiple cancers. However, the roles of genetic variants at 9p21.3 in esophageal squamous cell carcinoma (ESCC) development are largely unknown. We evaluated the genetic variants at 9p21.3 reported in cancer genome‐wide association studies with a case–control study including 2139 ESCC cases and 2273 controls in a Chinese population, and measured the mRNA expression levels of MTAP, CDKN2A, CDKN2B, and CDKN2B‐AS1 in paired ESCC tumor and adjacent normal tissues. We found that the G allele of rs7023329 was significantly associated with a decreased risk of ESCC with a per‐allele odds ratio of 0.84 (95% confidence interval, 0.77–0.91; P  = 2.95 × 10 −5 ). The rs7023329‐G allele was related to a high expression of MTAP ( P  = 0.020). The rs1679013‐C allele was independently associated with an increased risk of ESCC with a per‐allele odds ratio of 1.12 (95% confidence interval, 1.01–1.24; P  = 0.039). We also found that the carriers of the risk allele rs1679013‐C had lower expression of CDKN2B than non‐carriers ( P  = 0.035). CDKN2B was also significantly downregulated in ESCC tumor tissues compared with adjacent normal tissues ( P  = 3.50×10 −5 ). Therefore, our findings indicate that genetic variants at 9p21.3 may modulate the expression of MTAP and CDKN2B and contribute to ESCC susceptibility. This may further advance our understanding of the 9p21.3 locus in cancer development. Abstract : We evaluated the genetic variants at 9p21.3 reported in cancer GWAS with case‐control study including 2139 ESCC cases and 2273 controls in a Chinese population, and measured the mRNA expression levels of MTAP, CDKN2A, CDKN2B and CDKN2B‐AS1 in paired ESCC tumor and adjacent normal tissues. We found two independent variants in 9p21.3 (rs7023329 and rs1679013) associated with ESCC risk and provided additional evidence for the role of 9p21.3 locus in ESCC development. Our findings may further advance our understanding of 9p21.3 locus in cancer development.